The Effect of Health Education Using Leaflets on Knowledge of Childbirth in Primigravida Mothers - Deviani Fatimah; Yulianti (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2026)
Knowledge of pregnant women, especially primigravidas, plays a crucial role in preparing for childbirth. Lack of understanding can increase anxiety and the risk of complications. Leaflets are a practical, easy-to-understand, and self-study tool for health education. This study aimed to determine the effect of health education using leaflets on knowledge about childbirth among primigravida mothers. The study used a quasi-experimental design with a one-group pretest-posttest. The sample was 77 primigravida mothers who underwent examinations at Lagaligo Regional General Hospital I, East Luwu Regency, in September 2024. The research instrument was a standardized questionnaire whose validity was tested. Data were analyzed using univariate and bivariate tests using the Wilcoxon test with a significance level of p < 0.05. Before the intervention, 29 respondents (37.7%) had good knowledge, 25 (32.5%), and 23 (29.9%) had insufficient knowledge. After the intervention, good knowledge increased to 56 people (72.7%), sufficient knowledge decreased to 21 people (27.3%), and no respondents had poor knowledge. The Wilcoxon test results showed a p-value of 0.000, indicating a significant difference before and after leaflet distribution. Health education using leaflets effectively increased primigravida mothers' knowledge about childbirth. This media can be used as an educational tool in antenatal care to support safe childbirth. Further research using an experimental design with controls is recommended to evaluate the impact on childbirth behavior and readiness.